1986
DOI: 10.1038/320264a0
|View full text |Cite
|
Sign up to set email alerts
|

Serial and parallel processing of visual feature conjunctions

Abstract: Treisman and others have reported that the visual search for a target distinguished along a single stimulus dimension (for example, colour or shape) is conducted in parallel, whereas the search for an item defined by the conjunction of two stimulus dimensions is conducted serially. For a single dimension the target 'pops out' and the search time is independent of the number of irrelevant items in the set. For conjunctions, the search time increases as the set becomes larger. Thus, it seems that the visual syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

38
561
5
5

Year Published

1997
1997
2008
2008

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 831 publications
(609 citation statements)
references
References 8 publications
38
561
5
5
Order By: Relevance
“…However, most researchers have abandoned it (e.g. Wolfe, 1998a), as evidence accumulated to suggest that conjunction search can sometimes be quite efficient (Nakayama & Silverman, 1986) and that (as mentioned above), feature search can be inefficient when targets and distractors are very similar (Carter, 1982;Carter & Carter, 1981;Nagy & Sanchez, 1990). In addition, as is well known, sizable display set size slopes might be predicted by either a serial search or a limited-capacity parallel search in which processing is always parallel, but worsens when display set size increases (Townsend, 1976(Townsend, , 1990Wolfe, 1998a).…”
Section: Attentional Capacity Limits and The Serial/parallel Dichotomymentioning
confidence: 99%
“…However, most researchers have abandoned it (e.g. Wolfe, 1998a), as evidence accumulated to suggest that conjunction search can sometimes be quite efficient (Nakayama & Silverman, 1986) and that (as mentioned above), feature search can be inefficient when targets and distractors are very similar (Carter, 1982;Carter & Carter, 1981;Nagy & Sanchez, 1990). In addition, as is well known, sizable display set size slopes might be predicted by either a serial search or a limited-capacity parallel search in which processing is always parallel, but worsens when display set size increases (Townsend, 1976(Townsend, , 1990Wolfe, 1998a).…”
Section: Attentional Capacity Limits and The Serial/parallel Dichotomymentioning
confidence: 99%
“…FIT has been modified over the years since its introduction 37 , but the proposition that spatial attention is crucial for correct feature binding has remained. The theory has been the topic of some debate, especially regarding the question of whether features are processed in a qualitatively or quantitatively different way from conjunctions [38][39][40] . But the fact that spatial attentional deficits disrupt binding, while leaving feature detection relatively intact, lends strong support to the premise that feature detection and conjunction detection occur in qualitatively different ways.…”
Section: Space and Bindingmentioning
confidence: 99%
“…The red signal in traffic lights is one such example (Bugalski, 1967). To demonstrate the link between spatial attention, color, and depth perception, Nakayama and Silverman (1986) have shown that the visual detection of targets defined by conjunctions of color and depth in a visual search task is faster than the detection of targets defined by a single attribute. The implications of a correlation between perceived depth in geometric configurations and selective visual attention are discussed further by Nakayama, Shimojo, and Ramachandran (1990).…”
Section: The Contribution Of Color Stereopsismentioning
confidence: 99%
“…Then, a strong luminance or color cue combined with a strong geometric cue should produce shorter response latencies than a weaker luminance or color cue combined with a weaker geometric cue. Measuring response latencies to probe attentional mechanisms has proved successful in visual search experiments (e.g., Nakayama & Silverman, 1986), showing that certain combinations of visual cues produce significantly shorter response latencies than others in a given task context. Such effects are commonly explained in terms of facilitation or inhibition of attentional selection (e.g., Goolsby & Suzuki, 2001).…”
Section: The Contribution Of Color Stereopsismentioning
confidence: 99%
See 1 more Smart Citation